DESIGN OF A RAW MATERIAL INVENTORY CONTROL INFORMATION SYSTEM WITH THE JUST IN TIME (JIT) METHOD (CASE STUDY: CV. Sumber Rezeki): RANCANG BANGUN SISTEM INFORMASI PENGENDALIAN INVENTORY BAHAN BAKU DENGAN METODE JUST IN TIME (JIT) (STUDI KASUS : CV. SUMBER REZEKI) - Mu'tashim, Muhammad Afif; Suyatno, Dwi Fatrianto (Universitas Negeri Surabaya, 2024)
CV Sumber Rezeki is an MSME engaged in the production and sale of furniture based on requests from buyers or consumers which include household furniture, office interiors, kitchen sets, room sets, hotel interiors, apartment interiors and all types of wood-based craft work. The development of the industrial revolution 4.0 has a major impact on MSME development actors. However, not all MSMEs in Surabaya City utilize technology in their business processes. CV. Sumber Rezeki requires a strategy that can be used in planning raw material needs which aims to emphasize the purchase of raw material needs that are only used to make furniture or production through ordering requests from consumers or buyers. The results of this study indicate that the application can help CV. Sumber Rezeki in solving raw material inventory planning problems. This will make it easier for companies to determine the frequency of purchases, how many times each message should be sent, the amount of raw material orders for each message, the number of orders for each shipment, and the total cost of raw material inventory with Just In Time (JIT).